2006
DOI: 10.1038/sj.ijo.0803337
|View full text |Cite
|
Sign up to set email alerts
|

Muscle adiposity and body fat distribution in type 1 and type 2 diabetes: varying relationships according to diabetes type

Abstract: Objective: To compare the relationships between markers of total and regional adiposity with muscle fat infiltration in type 1 diabetic and type 2 diabetic subjects and their respective nondiabetic controls, and to document these relationships in type 1 diabetic subjects. Design: Cross-sectional study. Subjects: In total, 86 healthy, with type 1 diabetes, type 2 diabetes or control subjects. Each diabetic group was matched for age, sex and body mass index with its respective nondiabetic control group. Measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
0
20
2
Order By: Relevance
“…This is in contrast to the study by Park et al, who observed a small but significant difference in intrinsic muscle strength in a large group of older type 2 diabetic patients using dual-energy x-ray absorptiometry (DEXA) to evaluate muscle mass [40]. Overestimation of muscle mass by DEXA could account for the lower muscle quality observed [41], as could increased fat infiltration of the muscle, which is found more frequently in type 2 diabetic patients [42]. Analysis of magnetic resonance images allows exclusion of fat and fibrous tissue within muscle compartments.…”
Section: Discussioncontrasting
confidence: 54%
“…This is in contrast to the study by Park et al, who observed a small but significant difference in intrinsic muscle strength in a large group of older type 2 diabetic patients using dual-energy x-ray absorptiometry (DEXA) to evaluate muscle mass [40]. Overestimation of muscle mass by DEXA could account for the lower muscle quality observed [41], as could increased fat infiltration of the muscle, which is found more frequently in type 2 diabetic patients [42]. Analysis of magnetic resonance images allows exclusion of fat and fibrous tissue within muscle compartments.…”
Section: Discussioncontrasting
confidence: 54%
“…Compared with other studies done with other population [7, 20, 21], there was unique finding from our study. First, it is found that more subcutaneous fat in subjects with T1DM, and this is correlated to the state of diabetes.…”
Section: Discussioncontrasting
confidence: 54%
“…There was a study that compared abdominal fat distribution in different types of diabetes and their correlations [7]. However, it is done for different regions of the body such as fat in skeletal muscle and thigh, and it was performed in Canadians.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle dysfunction may lead to further inactivity and increased levels of IMAT precipitating a cycle of increased IMAT, insulin resistance, and muscle dysfunction. This close relationship between the muscle fibers and IMAT becomes particularly important in populations that are known to have increased IMAT, muscle dysfunction, and insulin resistance including individuals with diabetes [70] and survivors of stroke [28, 40] and spinal cord injury [39, 57, 58]. …”
Section: Imat and Metabolismmentioning
confidence: 99%